Wage Rigidities in an Estimated Dynamic, Stochastic, General Equilibrium Model of the UK Labour Market. (13th August 2013) - Faccini, Renato; Millard, Stephen; Zanetti, Francesco
Abstract : We estimate a New Keynesian model with matching frictions and nominal wage rigidities on UK data. We show that in a model with matching frictions, whether nominal wage rigidities are relevant or irrelevant for inflation dynamics depends on the parametrization. At the estimated equilibrium, we find that wage rigidities are irrelevant, despite improving the empirical performance of the model. The reason is that with matching frictions, marginal costs depend on unit labour costs and on an additional component related to search costs. Wage rigidities affect both components in opposite ways leaving marginal costs and inflation virtually unaffected.